Integrating Microsoft Office XP - Beskeen, David W. (Cengage Learning, 2002)
David W. Beskeen has authored or co-authored numerous computer books since 1992, including over 25 titles for Course Technology. David has written on PowerPoint, Word, Excel, Internet Explorer, Outlook, Windows, Livemotion, and other proprietary software packages. David also has teaching and consulting experience in the computer technology field